Pengaruh Pengetahuan Pajak dan Sanksi Pajak terhadap Kepatuhan Wajib Pajak dengan Kesadaran Wajib Pajak sebagai Variabel Moderasi - Murni Lestari; Dewi Sartika; Fatmayanti Fatmayanti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the influence of tax knowledge and tax sanctions on taxpayer compliance, as well as assess the role of taxpayer awareness as a moderation variable in individual taxpayers (WPOP) in West Aceh Regency. The research uses a quantitative approach with ex post facto design and survey methods. A sample of 100 respondents was selected through a random sampling technique based on the Slovin formula. Primary data were collected through a Likert scale questionnaire and analysis using instrument tests (validity and reliability), classical assumption tests, multiple linear regression analysis, and moderation regression tests to test hypotheses. The results of the study show that tax knowledge has a positive effect on taxpayer compliance. Tax sanctions also have a positive effect on taxpayer compliance. In addition, taxpayer awareness has been shown to moderate the relationship between tax sanctions and taxpayer knowledge. This means that the higher the taxpayer's awareness, the stronger the influence of tax knowledge and sanctions on taxpayer compliance. These findings are expected to be considered for tax authorities in formulating policies to increase compliance through education and strengthening tax awareness.